Pengaruh Gamifikasi Berbasis Tantangan Personal terhadap Kebugaran Jasmani pada Siswa Sekolah Dasar: Studi Kuasi-Eksperimental - Nak Mas Ashim Hanif; Januar Abdilah Santoso (Universitas Hamzanwadi, 2026)
Declining physical fitness among elementary school children has become a global concern, particularly in Southeast Asia, driven by sedentary lifestyles, urbanization, and low engagement in conventional physical education. This quasi-experimental study aimed to investigate the potential effects of an 8-week personal challenge-based gamification intervention on physical fitness and intrinsic motivation among elementary students. Thirty students (16 boys, 14 girls; mean age 10.3 ± 0.8 years) from SD Negeri 016 Sungai Kunjang participated in a one-group pretest-posttest design. The intervention was integrated into regular physical education classes (two 45-minute sessions per week). Physical fitness was measured using the FITNESSGRAM battery, while intrinsic motivation was assessed with the Indonesian-adapted Intrinsic Motivation Inventory (IMI). Gamification engagement was monitored via structured observation. Significant improvements were observed in all fitness components: cardiovascular endurance (29.5%, d = 1.18), muscular strength (34.8%, d = 1.24), muscular endurance (30.3%, d = 1.06), and flexibility (21.3%, d = 0.88). Overall intrinsic motivation increased by 35.0% (d = 1.91), with high engagement rates (94.2% participation). This study provides preliminary evidence that personal challenge-based gamification may be associated with improved physical fitness and intrinsic motivation. The low-cost approach shows potential for enhancing student engagement in physical education, although the lack of a control group requires cautious interpretation and further rigorous research.